Synthesis, characterization and analytical study of tellurated Schiff base of bis[2-(3-nitrobenzylideneamino)-5-nitrophenyl]telluride and its complexation reactions with Mn(II), Co(II) and Ni(II) ions - Al-Fregi, Adil Ali; Adnan, Mayada Abdulaa (European Journal of Chemistry, 2016)
Reaction of 2-amino-5-nitrophenylmercuric chloride with 3-nitro benzaldehyde gave 2-(3-nitrobenzylideneamino)-5-nitrophenylmercuric chloride (1). Reaction of the mercurated Schiff bases 1 with tellurium tetrabromide in 2:1 mole ratio gave the tellurated Schiff bases, bis[2-(3-nitrobenzylidineamino)-5-nitrophenyl] tellurium dibromide (2). Reduction of compound 2 by hydrazine hydrate gave the corresponding telluride, bis[2-(3-nitro benzylideneamino)-5-nitrophenyl]telluride (3). Complexation reactions of equilibrium mole ratios compound 3 with MnCl2.4H2O, CoCl2.6H2O and NiCl2.6H2O gave the corresponding complexes, i.e compounds 4-6, respectively. All the prepared compounds were characterized by elemental analysis, conductivity measurements and 1H and 13C NMR, FT-IR and UV-visible spectroscopic data. These data suggested that the compound 3 coordinate with metal ions as tridentate ligand. The molar conductivity study indicated compounds 1-3 are neutral and behave as non-electrolytes in DMSO solvent at room temperature while compounds 4-6 behave as 1:1 electrolytes in the same conditions. The molar ratio method was used to determine metal-ligand ratio, which was found as 1:1, metal: ligand. The thermal analysis of compounds 2 and 3 were also investigated and discussed.